ANSWER
The third option is the correct answer
[tex] log3(x + 4) = log(3) + log(x + 4)[/tex]
EXPLANATION
The expression given to us is
[tex] log3(x + 4) = log(3) + log(x + 4) [/tex]
This logarithmic expression is of the form
[tex] log(A \times B)[/tex]
So we use the multiplication law of logarithm which is given by
[tex] log(A \times B) = log( A ) + log( B ) [/tex]
We therefore set
[tex]A = 3[/tex]
[tex]B = x + 4[/tex]
The given expression now becomes,
[tex] log3(x + 4) = log(3) + log(x + 4) [/tex]